Spartalizumab in metastatic, well/poorly differentiated neuroendocrine neoplasms - Yao, James C.; Strosberg, Jonathan; Fazio, Nicola; Pavel, Marianne Ellen; Bergsland, Emily; Ruszniewski, Philippe; Halperin, Daniel M.; Li, Daneng; Tafuto, Salvatore; Raj, Nitya; Campana, Davide; Hijioka, Susumu; et al. (Endocrine-Related Cancer, 2021)
Spartalizumab, a humanized anti-programmed death protein 1 (PD-1) MAB, was evaluated in patients with well-differentiated metastatic grade 1/2 neuroendocrine tumors (NET) and poorly differentiated gastroenteropancreatic neuroendocrine carcinomas (GEP-NEC). In this phase II, multicenter, single-arm study, patients received spartalizumab 400 mg every 4 weeks until confirmed disease progression or unacceptable toxicity. The primary endpoint was confirmed overall response rate (ORR) according to blinded independent review committee using response evaluation criteria in solid tumors 1.1. The study enrolled 95 patients in the NET group (30, 32 and 33 in the thoracic, gastrointestinal, and pancreatic cohorts, respectively), and 21 patients in the GEP-NEC group. The ORR was 7.4% (95% CI: 3.0, 14.6) in the NET group (thoracic, 16.7%; gastrointestinal, 3.1%; pancreatic, 3.0%), which was below the predefined success criterion of ≥10%, and 4.8% (95% CI: 0.1, 23.8) in the GEP-NEC group. In the NET and GEP-NEC groups, the 12-month progression-free survival was 19.5 and 0%, respectively, and the 12-month overall survival was 73.5 and 19.1%, respectively. The ORR was higher in patients with ≥1% PD-L1 expression in immune/tumor cells or ≥1% CD8+ cells at baseline. The most common adverse events considered as spartalizumab-related included fatigue (29.5%) and nausea (10.5%) in the NET group, and increased aspartate and alanine aminotransferases (each 14.3%) in the GEP-NEC group. The efficacy of spartalizumab was limited in this heterogeneous and heavily pre-treated population; however, the results in the thoracic cohort are encouraging and warrants further investigation. Adverse events were manageable and consistent with previous experience.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Gastroenteropancreatic neuroendocrine carcinomas; Neuroendocrine tumors; Programmed death protein 1 inhibitor; Spartalizumab